The Role and Impact of Government Audit Practices in Maintaining Public Trust - Syam, Hasnidar (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study explores the critical role of government audit practices in promoting transparency, accountability, and public trust within governance systems. It examines the current state of government audit practices, identifies challenges and limitations, and proposes strategies for enhancing audit effectiveness. Research Design and Methodology: Employing a systematic literature review approach, the research design involves comprehensive searches across academic databases to identify relevant studies Findings and Discussion: Findings indicate that robust audit practices are associated with lower levels of corruption, higher government effectiveness, and enhanced public trust. However, challenges such as resource constraints and political interference hinder audit effectiveness. Implications: This research contributes to advancing the effectiveness and relevance of government audit practices, thereby promoting good governance and accountability within governmental entities.